Adesione batterica e fungina a materiali protesici del cavo orale - Fabrizio Cavallini; Simone Cagnacci; Elisabetta Maioli; Lionello Lagorio; Damiano Gibelli; Simona Roveta; Anna Marchese; Eugenio A. Debbia (Microbiologia Medica, 2005)
Introduction.The microbial adhesion to dental material was studied employing a acrylic resin and representative microrganisms. Method. Bacterial suspensions (about 108 CFU/ml) were mixed to dental material with different surface finishes. Bacterial counts were carried out before and after 1 hour at 37°C.A tube without dental material was used as control.The same experiments were also performed at the presence of saliva. Results. Candida albicans demonstrated to adhere to free energy material at an incidence 64% while Staphylococcus aureus and Streptococcus oralis showed more adhesive properties for roughness material (34 and 52% respectively). The presence of saliva influenced the adhesiveness to all materials with the exception of S. aureus that increased from 20 to 29% the number of cells on the surface of free energy material. Conclusion. The surface finishes appeared did not significantly influence the adhesion of microrganisms to this material.